Schizotypy and altered hemispheric asymmetries: The role of cilia genes. (30th December 2019) - Schmitz, Judith; Fraenz, Christoph; Schlüter, Caroline; Friedrich, Patrick; Kumsta, Robert; Moser, Dirk; Güntürkün, Onur; Genç, Erhan; Ocklenburg, Sebastian
Highlights: AHI1 is a gene that has been associated with schizophrenia and body asymmetries. AHI1 DNA methylation predicts schizotypy and language laterality in healthy adults. AH11 DNA methylation predicts microstructural asymmetry in the planum temporale. Our results support a shared molecular basis of schizotypy and laterality. Abstract: Schizophrenia patients have a higher probability of altered structural and functional differences between the left and right hemisphere. Schizotypy as its nonclinical manifestation has been related to a higher incidence of non-right-handedness and atypical right-hemispheric language dominance. It has been suggested that genes involved in cilia function might link brain asymmetry and neurodevelopmental disorders. We assessed DNA methylation in the promoter regions of seven candidate genes involved in cilia function and psychiatric disorders from buccal cells and investigated their association with schizotypy and language lateralization in 60 healthy adults. Moreover, we determined microstructural properties of the planum temporale in a subsample of 52 subjects using neurite orientation dispersion and density imaging (NODDI). We found a significant association between schizotypy and DNA methylation in the AHI1 promoter region. Moreover, AHI1 DNA methylation significantly predicted language lateralization and asymmetry in estimated planum temporale neurite density. Finally, stronger leftward asymmetry in estimated neurite density was associated with a more pronounced right ear advantage (left hemisphere dominance) in the forced-right condition of the dichotic listening task, measuring attentional modulation of language lateralization. Our results are in line with a shared molecular basis of schizotypy and functional hemispheric asymmetries that is based on cilia function.